IMPLEMENTASI PEMBELAJARAN TERPADU DI KELAS 5 SD NEGERI BANJAR AGUNG 4 (JS (JURNAL SEKOLAH), 2022)
Abstract: Implementation of Integrated Learning in Grade 5 of SD Negeri Banjar 4. The purpose of this study is to describe the implementation of integrated learning in grade 5 of SD Negeri Banjar Agung 4 and to describe the obstacles faced by teachers in integrated learning. The type of research used is descriptive qualitative method. The subjects in this study were 5th grade teachers at SD Negeri Banjar Agung 4. The data collection techniques used in this study were observation, interviews and documentation. The results of this study indicate that the implementation of integrated learning in grade 5 with integrated learning makes learning more innovative and varied so that students are not easily bored and seen from its implementation by combining one material with other materials it provides a meaningful experience. In addition, there are also teacher barriers during the implementation of integrated learning, namely sometimes the mother is too comfortable when discussing a material so that she forgets to link the next material. With this integrated learning, students will get hands-on experience and increase their knowledge and skills in ongoing learning. Keywords : Implementation, Integrated Learning, LearnersAbstrak: Implementasi Pembelajaran Terpadu di Kelas 5 SD Negeri Banjar 4. Tujuan penelitian ini untuk mendeskripsikan implementasi pembelajaran terpadu di kelas 5 SD Negeri Banjar Agung 4 dan untuk menguraikan kendala yang dihadapi guru dalam pembelajaran terpadu. Jenis penelitian yang digunakan adalah metode kualitatif dekriftif. Adapun subjek dalam penelitian ini adalah guru kelas 5 SD Negeri Banjar Agung 4. Teknik pengumpulan data yang digunakan dalam penelitian ini berupa observasi, wawancara dan dokumentasi. Hasil penelitian ini menunjukkan  bahwa implementasi pembelajaran terpadu di kelas 5 dengan adanya pembelajaran terpadu membuat pembelajaran menjadi lebih inovatif dan bervariatif sehingga peserta didik tidak mudah jenuh serta dilihat dari pelaksanaannya dengan penggabungan materi satu dengan materi lainnya memberikan pengalaman yang bermakna. Selain itu juga terdapat hambatan guru pada saat pelaksanaan pembelajaran terpadu yaitu terkadang ibu tuti terlalu nyaman ketika membahas sesuatu materi hingga lupa menggaitkan materi selanjutnya. Dengan adanya pembelajaran terpadu ini, peserta didik akan mendapatkan pengalaman secara langsung dan meningkatkan pengetahuan serta keterampilan pada pembelajaran berlangsung. Kata kunci: Implemenntasi, Pembelajaran Terpadu, Peserta didik